Evaluation of the efficacy of the utilization of the imipramine for patients with allergic rhinitis - Diaa El Din El Hennawi; Mohamed Rifaat Ahmed; Yasser T Madian; Mohammed T El-Tabbakh; Ibrahim Hassan Ibrahim (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Background: allergic rhinitis is an infl ammatory process of the upper respiratory tract with a continuous symptom that last for hour or more with symptom affect patient's work and quality of life.  Methodology: a randomized controlled trial in which we enrolled 284 patients with allergic rhinitis for periods longer than 4 days/week and for more than 4 consecutive weeks divided into two groups. Group A (n=142) received Imipramine 75 mg/day for 90 days .Group B (n=142), the control group, received desloratadine 5 mg / day for 90 days. Results: The mean visual analogue score nasal symptoms intensity (sneezing, Nasal obstruction, watery rhinorrhea and itchy nose) showed a statistically signifi cantly improvement in group A (treated with Imipramine) compared with group B (treated with desloratadine) after the same treatment period. Conclusion: Imipramine could be used in treatment patients with allergic rhinitis as it is effective as an antihistaminic besides its main action in reliving psychosocial stresses.